Duplex sequencing uncovers recurrent low-frequency cancer-associated mutations in KMT2A-rearranged infant acute leukemia - Pilheden, Mattias; Hagström Andersson, Anna (Lund University, 2022)
This dataset includes Duplex sequencing and targeted next generation sequencing (NGS) of 20 Infants and 7 Children with acute lymphoblastic leukmia.

All patients had an underlying rearrangement of the KMT2A gene, either KMT2A::MLLT3 (n=5), KMT2A::AFF1 (n=12), KMT2A::MLLT1 (n=8) or KMT2A::MLLT10 (n=2). The median age of the cohort was 7 months.

Diagnostic sample from peripheral blod (n=11) or bone marrow (n=16) underwent the duplex sequencing library preparation as described in https://doi.org/10.1073/pnas.1208715109 and sequenced on the NextSeq 500 (Illumina, San Diego, CA, USA).

A subset of variants were validated by targeted multiplex-PCR followed by NGS. In six patients with available relapse samples, a screening of diagnostic variants was performed by multiplex-PCR and NGS. All targeted sequencing libraries were prepared with Nextera XT DNA Sample Preparation Kit (Illumina) and sequenced on the Illumina MiSeq.
Keywords: Sequence analysis; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi